Efforts to Increase Interest in Learning Arabic Mufradat with Index Card Match Method on Student of Class IX B Mts Nu Tmi Pujon - Mila, Zahrotul; Firdiansyah, Yhadi; Agil, Idrus Muchsin Bin (Proceeding of International Conference on Islamic Education (ICIED); Vol 4 No 1 (2019): Proceeding of International Conference on Islamic Education (ICIED), 2019)
One of the problems at school today is that students' lack of interest in learning Arabic, students feel bored and difficult when learning mufrodat and less interesting mecdia used. The study aims (1) to determine students' interest in learning mufrodat in class IX B MTs NU TMI Pujon before using the index card match media. (2) to find out the students' interest in learning mufrodat in class IX B MTs NU TMI Pujon after using the index card match media. (3) to determine the effect of the use of the media index card match to increase student interest in learning mufrodat in class IX B MTs NU TMI Pujon. The methodology used in this research is classroom action research. The subjects in this study were 29 students of class IX B. The results of this study were: (1) students' interest in learning mufrodat before using the media index card match. (2) student interest in learning in mufrodat learning after using the index card match media (3) the effect of media index card match on student learning interest in mufrodat learning.